Pengaruh jam kerja, modal, pendidikan dan tenaga kerja terhadap pendapatan UKM sektor perdagangan di Kota Sungai Penuh - Yogi Seprianto; Zulfanetti Zulfanetti; Nurhayani Nurhayani (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2021)
The purpose of this study was to determine the effect of capital, working hours, education, social and economy simultaneously on increasing income Trade Sector UKM in Sungai Penuh City and to know the social and economic development of UKM Trade sector in Sungai Penuh City. This research is a research with a quantitative approach with a population of 157 SMEs. The sampling technique used is proportionate stratified random sampling in order to obtain a total sample of 113 samples. The data collection technique used a questionnaire. Classical assumptions use normality test, multicollinearity test and heteroscedasticity test. The data analysis technique to answer the hypothesis uses multiple linear regression analysis techniques. The results of the assumptions are. Social development affects the income of trading SMEs in Sungai Penuh City. variable working hours, capital, education, and labor have a significant effect on the income of trading SMEs in Sungai Penuh City partially. The four variables, namely working hours, education capital, and labor have an effect on the income of trading SMEs in Sungai Penuh City.